Ekspresi Faktor Antiangiogenesis Thrombospondin-1 (TSP-1) dan Angiostatin Kanker Payudara Invasif - Ambar Mudigdo; Dyah Ratna Budiani (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2018)
Background Angiogenesis is one of the characteristics of malignant cancer cells. Angiogenesis activity considered as one of many determinants of prognosis of invasive breast cancer. The body has endogenous factors that act as antiangiogenesis, such as thrombospondin-1 (TSP1) and angiostatin. TSP1 is an antiangiogenesis factor that is dependent on wild-type p53. TSP-1 expression is induced by the transcription factor p53 WT. In some breast malignancies occurs mutations in the p53 gene, so TSP1 can not be expressed. The absence of TSP1 expected to bring a worse prognosis. Study of antiangiogenesis protein expression is expected to be used as an indicator of prognosis in breast cancer invasive ductal mammary carcinoma which divided into four sub-types: luminal A; luminal B; Her2 (over-expression) and triple negative/basal-like. This study is to analyzed TSP-1 and angiostatin of invasive breast cancer. Methods A total of 20 paraffin blocks of breast cancer tissue invasive ductal carcinoma from Pathology Anatomy RS Dr. Moewardi in 2013 were divided into four groups based on the expression status of estrogen receptors, progesterone receptors and Her2/neu as follows: luminal A subtype (ER+/PR+/Her2 negative); sub-type luminal B (ER-/PR and Her2 positive); Her2 over expression subtype (ER-/PR-/Her2 over-expression); and triple negative subtypes (basal-like tumors). Technique immunohistochemical ABC (avidin-biotin complex) used in special stains to measure the expression of TSP-1 and angiostatin, using monoclonal antibodies anti-human TSP-1 and anti-human angiostatin. Expression values are expressed in scale IDS, with a value range 0 to IDS 300. Analysis of the data used is difference test paired between groups (p